Cardio‐ankle vascular index and circulating CD34‐positive cell levels as indicators of endothelial repair activity in older Japanese men. Issue 6 (28th March 2019) - Shimizu, Yuji; Yamanashi, Hirotomo; Noguchi, Yuko; Koyamatsu, Jun; Nagayoshi, Mako; Kiyoura, Kairi; Fukui, Shoichi; Tamai, Mami; Kawashiri, Shin‐Ya; Kondo, Hideaki; Maeda, Takahiro
Abstract : Aim: The cardio‐ankle vascular index (CAVI) reflects functional arterial stiffness, which is related to endothelial dysfunction. CD34‐positive cells carry out an important function in endothelial repair. However, there have been no reports assessing the association between CAVI and the number of circulating CD34‐positive cells. Methods: We carried out a cross‐sectional study of 249 Japanese men, aged 60–69 years, who underwent annual health checkups between 2013 and 2015. As individuals with high levels of circulating CD34‐positive cells might indicate the influence of consumptive reduction of circulating CD34‐positive cells as a result of aggressive endothelial repair, participants were stratified by circulating CD34‐positive cell levels, using the median value in this population (0.95 cells/μL) as the cut‐off. Results: For participants with low circulating CD34‐positive cell levels, logarithmic values of circulating CD34‐positive cells were inversely associated with CAVI (multivariable standardized parameter estimate [β] = −0.22, P = 0.014), but not for participants with high levels (β = −0.04, P = 0.638). In addition, even when no significant associations between CAVI and carotid intima‐media thickness were detected for participants with low circulating CD34‐positive cell levels (β = −0.02, P = 0.865), significant positive associations were identified for participants with high levels (β = 0.22, P = 0.028). Conclusions: As circulating CD34‐positive cell count might indicate endothelial repair activity, the present results show that CAVI is affected by insufficient endothelial repair in individuals with low circulating CD34‐positive cell counts. Our results also show that a positive association between CAVI and carotid intima‐media thickness exists only in individuals with aggressive endothelial repair, which indicates the presence of organic arterial disease, such as atherosclerosis.Geriatr Gerontol Int 2019; 19: 557–562 .